Preventing alcohol-exposed pregnancy among American-Indian youth. Issue 4 (3rd July 2016) - Jensen, Jamie; Kenyon, DenYelle Baete; Hanson, Jessica D.
Abstract: Research has determined that the prevention of alcohol-exposed pregnancies (AEP) must occur preconceptually, either by reducing alcohol intake in women planning pregnancy or at risk for becoming pregnant, or by preventing pregnancy in women drinking at risky levels. One such AEP prevention programme with non-pregnant American-Indian (AI) women is the Oglala Sioux Tribe (OST) Changing High-risk alcohOl use and Increasing Contraception Effectiveness Study (CHOICES) Programme, which shows promise in reducing AEP risk in AI women aged 18 or older. A community needs assessment was conducted with key informant interviews and focus groups with an emphasis on how to expand OST CHOICES. To identify relevant inter-related themes, a content analysis was conducted on qualitative feedback from the focus groups and interviews. Altogether, key informant interviews were completed with 25 health and social service professionals. Eight focus groups were held with 58 AI participants, including adult women of child-bearing age, elder women, and adult men. Several sub-themes regarding the prevention of AEP with youth were identified, expanding the OST CHOICES curriculum into the schools, and the role of family and culture within AEP prevention.